2016
DOI: 10.4314/njbas.v24i1.8
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method of Crude Oil Analysis Using FT-IR Spectroscopy

Abstract: This study determines the viability of the use of Fourier Transform Infrared (FTIR) spectroscopy as a substitute to traditional petroleum geochemical methods for crude oil characterisation. IR spectra of Crude oil sample containing a mixture of both degraded (sample 151) and non-degraded (sample 145) oils at different concentrations were determined. The IR fingerprints agree with results obtained from GC analysis. Partial least square regression analysis was used to predict saturates for omitted mixtures (10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Degradation of crude oil components by the potent bacterial strains was further confirmed by FTIR analysis. FTIR analysis has been used by various researchers to classify the dominant petroleum hydrocarbon fractions in the contaminated sites based on the carbon chain length 60,61,37 . Application of FTIR study was also reported in the study of microbial degradation of hydrocarbon contaminants 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of crude oil components by the potent bacterial strains was further confirmed by FTIR analysis. FTIR analysis has been used by various researchers to classify the dominant petroleum hydrocarbon fractions in the contaminated sites based on the carbon chain length 60,61,37 . Application of FTIR study was also reported in the study of microbial degradation of hydrocarbon contaminants 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…A Fourier transform infrared (FTIR) spectroscopy instrument would be the preferred choice for an in situ downhole application due to the high modulation frequencies that can be achieved with the method. In the oil and gas industry FTIR spectroscopy has been applied in combination with chemometrics and statistical data analysis to achieve rapid rig site chemical analysis of crude oils (Abdulkadir et al 10 , Aske et al 11 , and Hannisdal et al 12 ). However, the challenge confronting realization of this concept for in situ downhole application remains in the limitations of the state of the art in infrared detector technologies.…”
Section: Near Zero Index Perfect Metasurface Absorber Using Inverted mentioning
confidence: 99%
“…In this study, similar to the fingerprint method for identifying chemical substances, FT-IR is considerably powerful, rapid, simple and relatively cost effective. Recent studies have shown that FT-IR is capable of identifying the adulterated compounds in palm oil and reheated palm oil (Che Man et al, 2014;Lim et al, 2018;Faridah et al, 2015), determining purity of olive oil and crude oil (Rohman and Che Man, 2010;Abdulkadir et al, 2016) and authentify avocado oil (Rohman et al, 2015). Moreover, Ang et al (2019) and Wong et al (2019) have reported the rapid quantification of processing contaminants [such as 3-mono-chloropropane-1,2diol (MCPD) esters] in palm-based cooking oil using FT-IR spectroscopy.…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%